The factors that influence level of awareness on sexual harassament case study in Jabatan Kerja Raya (JKR) Melaka / Manirrah Alias and Nurul Nor Rashidah Leana Rosli - Alias, Manirrah; Rosli, Nurul Nor Rashidah Leana (Faculty of Administrative Science and Policy Studies, 2012)
The studies were focusing on the factors that influence level of awareness on sexual harassment. The studies were conducted at Jabatan Kerja Raya Melaka among the employees in different department which are from Mechanical division, Electrical division, Corporate division, Administration division, Quantity Surveyor division, Maintenance division, Building division, Architect division, Armforce division and Roads division. In this study, from 650 respondent, only 242 respondent will be the sample size and answer the questionnaire. This study was conducted aim to determine level of awareness on sexual harassment, to determine the significant relationship between factors and level of awareness on sexual harassment and to identify the most factors that influence level of awareness on sexual harassment. After conducted the several test, the research find that, there are moderate level of awareness on sexual harassment among employees at Jabatan Kerja Raya Melaka. Besides that, there are low relationship between mass media, government, and attitude and behavior. While, there is negligible relationship between training and education and level of awareness on sexual harassment.